Keith D. Stanglin, Thomas H. McCall, Jacob Arminius. Theologian of Grace, Wydawnictwo Oxford University Press, New York 2012, ss. 240. - Dorocki, Damian (Teologia w Polsce, 2020)
Recenzja książki: Keith D. Stanglin, Thomas H. McCall, Jacob Arminius. Theologian of Grace, Wydawnictwo Oxford University Press, New York 2012, ss. 240.